Transgender and nonbinary activism among social work students in the US: The role of ally behavior and a critical orientation to social justice. Issue 2 (3rd April 2022) - Holloway, Brendon T.; Atteberry-Ash, Brittanie; Kattari, Leonardo; Harrop, Erin; Walls, N. Eugene
ABSTRACT: Social workers are expected to serve and advocate for marginalized communities, including but not limited to transgender and nonbinary communities (TNB). However, the extent to which social workers meet this expectation is unknown. Using data from a 2019–2020 survey of students who were enrolled in U.S. social work programs ( N = 725), this study examined the predictors for engaging in TNB activism, including interaction effects between subdomains of the adapted Ally Identity Measure and students' personal endorsement of a Critical Orientation to Social Justice. We found that both students identifying as LGBQ and having more TNB people in one's social network were associated with an increase in engaging with TNB activism. Among our social work educational variables, we found that students who have a mixed micro/macro focus, those who had taken a course on power, privilege, and oppression, and those who had engaged in intergroup dialogue were more likely to engage in TNB activism. Finally, we found that the interaction effects between the Critical Orientation to Social Justice Scale and two of the adapted Ally Identity Measure subdomains were significant.